A child in pain: A psychologist's perspective on changing priorities in scientific understanding and clinical care. Issue 2 (4th August 2020) - Craig, Kenneth D.
Abstract: My research and clinical career followed a trajectory of increasing appreciation for the importance of social factors as determinants of pain experience and expression. The social contexts of children's lives determine whether infants and children are exposed to pain, how socialization in family and ethnocultural contexts lead to pain as a social experience, comprised of thoughts and feelings as well as sensory input, how others shape pain experience and expression, less so for automatic/reflexive features than purposeful representations, and how other's appraisals of children's pain reflect the observer's unique background and capacities for intervening in the child's interests. A greater understanding of the social dimensions of pain, as reflected in the social communication model of pain, would support innovation of psychological and social interventions.